2017
DOI: 10.1007/s11365-017-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance in family SMEs: the moderating effects of family, women, and strategic involvement in the board of directors

Abstract: Entrepreneurial success in family SMEs is largely determined by the knowledge, skills, and new ideas contributed by board directors, the most important actors in the formulation of corporate strategy and decision making. The composition of family SME boards has traditionally been homogeneous, as such boards usually comprise male family members. Boards' contributions, however, depend on their level of diversity and strategic involvement. This study analyzes the moderating effects of two main sources of board di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 126 publications
2
72
1
4
Order By: Relevance
“…The power distribution inside the firm depends on the dynamics within the board of directors (Arzubiaga et al, 2018). Hence, independent directors who are supposed to be unbiased concerning inside interests, and the role played by female board members, or the presence of directors representing pension funds, financial institutions, or other institutional investors, can have influential consequences on the corporate governance of Latin American firms, and ultimately, in the discretionary managerial decision-making power regarding the quality of earnings.…”
Section: Resultsmentioning
confidence: 99%
“…The power distribution inside the firm depends on the dynamics within the board of directors (Arzubiaga et al, 2018). Hence, independent directors who are supposed to be unbiased concerning inside interests, and the role played by female board members, or the presence of directors representing pension funds, financial institutions, or other institutional investors, can have influential consequences on the corporate governance of Latin American firms, and ultimately, in the discretionary managerial decision-making power regarding the quality of earnings.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, research within a services sector context, manifested that EO affects business performance only in small and not in large companies (Núñez-Pomar, Prado-Gascó, Sanz, Hervás, & Moreno, 2016). Nonetheless, in small family businesses the relationship between EO and business performance is stronger when there are lower levels of family involvement in the company's board of directors (Arzubiaga, Iturralde, Maseda, & Kotlar, 2018). In addition, studies have shown the positive impact of EO on SME's performance when the SME becomes active in international markets (see Chew, 2018).…”
Section: Links Between Mo Eo and Performancementioning
confidence: 99%
“…In this paper, we focus on SME directors, who are responsible for the internationalization strategy of the firm, (Rivas et al, 2009;Rivas et al, 2012;Arzubiaga et al, 2018) and following recent studies (e.g., Pergelova et al, 2018) we examine potential gender differences in exporting activity of the firms. To do so, we draw on the Resource Based View (RBV) and Resource Dependency Theory (RDT), which are well-established frameworks that are used to explain the internationalization of SMEs (Pfeffer & Salancik, 1978;Duran & Jordan, 2012;Laufs & Schwens, 2014).…”
Section: Introductionmentioning
confidence: 99%